Judgment, shame, and coercion: the criminal legal system and reproductive autonomy - Ginny Garcia-Alexander; Melissa Thompson (Health & Justice, 2024)
Abstract Background A growing body of research has called attention to limitations to reproductive autonomy in both women who are socially disadvantaged and in those who have had contact with the criminal legal (CL) system. However, it is unclear whether CL system contact influences contraceptive use patterns and how these processes unfold. We utilize a mixed-methods approach to investigate whether history of arrest is associated with receipt of contraceptive counseling, use of long-term contraception, sterilization, and subsequent desire for reversal of sterilization. We further consider how agents in and around the CL system may influence women’s reproductive decisions and outcomes (856 survey respondents; 10 interviewees). Results We observe that women who have been arrested more commonly report receipt of contraceptive counseling and sterilization. They are also significantly more likely to want their sterilization reversed. Our in-depth interviews suggest that women with CL contact experience considerable shame, and in some cases, coercion to limit fertility from various agents in and outside the criminal legal system including medical providers, Parole/Probation Officers (POs), guards, and family members. Conclusions Our findings suggest the need for ongoing attention to how exposure to this system may promote uneven use of certain forms of contraception and dissatisfaction, i.e., desire for reversal of sterilization, among these women. Findings further suggest that de-emphasizing the CL system as a means through which to address reproductive needs should be considered.